Low expression of GSTP1 in the aqueous humour of patients with primary open‐angle glaucoma. Issue 6 (17th February 2021) - Liu, Aihua; Wang, Liming; Feng, Qiang; Zhang, Dandan; Chen, Kexi; Yiming, Guli Humaer; Wang, Qiong; Hong, Yaru; Whelchel, Amy; Zhang, Xiaomin; Li, Xiaorong; Dong, Lijie
Abstract: Primary open‐angle glaucoma (POAG) is characterized by irreversible neurodegeneration accompanied by visual field defects and high intraocular pressure. Currently, an effective treatment is not available to prevent the progression of POAG, other than treatments to decrease the high intraocular pressure. We performed proteomic analysis of aqueous humour (AH) samples from patients with POAG combined with cataract and patients with cataract to obtain a better understanding of the pathogenesis of POAG and explore potential treatment targets for this condition. Samples were collected from 10 patients with POAG combined with cataract and 10 patients with cataract. Samples from each group were pooled. A high‐resolution, label‐free, liquid chromatography‐tandem mass spectrometry‐based quantitative proteomic analysis was performed. In total, 610 proteins were identified in human AH samples from the two groups. A total of 48 up‐regulated proteins and 49 down‐regulated proteins were identified in the POAG combined with cataract group compared with the control group. Gene Ontology (GO) analysis revealed key roles for these proteins in inflammation, immune responses, growth and development, cellular movement and vesicle‐mediated transport in the biological process category. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis indicated the down‐regulated expression of glutathione S‐transferase P (GSTP1) in the glutathione metabolism signalling pathway in the POAG combined with cataract group. Additionally, certain significantly differentially expressed proteins in the proteomic profile were verified by enzyme‐linked immunosorbent assay (ELISA). GSTP1 levels were reduced in the human AH samples from the POAG combined with cataract group, based on the results of ELISA and proteomic profiling. Therefore, GSTP1, a redox‐related marker, may be involved in the pathological process of POAG and may become a treatment target in the future.